Fortresses and dungeons: the persistence of the sexual division of occupations in contemporary society (ex æquo, 2013)
While general indicators of womens and mens activity typically lead the debate on gender equality in the labour market, distribution across occupations has been paid less attention. This article begins by reviewing a number of studies that help understand occupational segregation. Afterwards, data from the National Statistics Office (Portugal) regarding the first decade of the 21st century are examined. Growth in intelectual and scientific occupations coexists with stability or even increase in occupations at the lower end of education and status ladders, which remain strongly gendered. While among the highly schooled segments of the population masculine fortresses are under assault, occupations with poorer working conditions resemble, for women, dungeons from which escape is difficult.
Keywords: occupations, segregation, labour market, equality